Companion of the 2018 ACM Conference on Computer Supported Cooperative Work and Social Computing 2018
DOI: 10.1145/3272973.3273010
|View full text |Cite
|
Sign up to set email alerts
|

Sociotechnical Systems of Care

Abstract: The goal of this workshop is to bring together CSCW audiences who engage in studies and interventions related to care work. Our aims are to understand how care has been conceptualized in the extant CSCW community, identify core issues and concerns, and formalize how CSCW concepts could be used as a lens to inquire into this domain. We will explore the following themes: the invisibility of care work; the evolution of care labor; how care can often be sentimentalized, formalized, or infantilizing; and how we can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…CSCW scholarship has drawn attention to the performance of caring labour with sociotechnical systems and the data generated through these activities [11,41]. Coordination, collaboration, cooperation, and care in stewarding the data of others are matters of concern that will only grow.…”
Section: Discussionmentioning
confidence: 99%
“…CSCW scholarship has drawn attention to the performance of caring labour with sociotechnical systems and the data generated through these activities [11,41]. Coordination, collaboration, cooperation, and care in stewarding the data of others are matters of concern that will only grow.…”
Section: Discussionmentioning
confidence: 99%
“…There is a growing concern for care in other sociotechnical encounters and a spectrum of activities from education [43], to appropriating data collection for affordable housing [89], to logistics of humanitarian aid [37], to maintenance and repair of technologies and their associated sites of development and modification [38], [39], [83], and even to the relationships subjects have with research projects [36]. Recognizing this breadth, Toombs, et al [82] have shown a particular investment in thinking through the complexities and complicities of care. Indeed, a common theme of care work both inside and beyond HCI is that it involves seemingly simultaneous exercises of doing good while making compromises.…”
Section: Care and Its Complexitiesmentioning
confidence: 99%
“…This group of workshop organizers was selected to reflect the diversity we hope to recruit for participants as well as diversity in methods and topical expertise. Organizers have successfully (co-)organized workshops in the past at CHI [3,14], CSCW [21], NordiCHI [13], GROUP [11], and ICWSM [9,10]. Stevie Chancellor is a PhD Candidate in Human Centered Computing at Georgia Tech.…”
Section: Organizersmentioning
confidence: 99%